2014
DOI: 10.1163/22134468-00002031
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Questionnaire on Time: Feeling of the Passage of Time

Abstract: The aim of our studies was to design a Metacognitive Questionnaire on Time (MQT) that assesses inter-individual variations in the awareness of factors affecting the experience of the passage of time. In the first study, 532 young adults were asked to reply to an initial questionnaire consisting of 106 questions relating to many different factors (e.g., psychostimulant, body temperature, age, attention) that could affect how time is perceived. Factorial analyses allowed us to extract two discriminant factors, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…A long tradition (going back in formal models to Treisman, 1963) has proposed that people possess an arousalsensitive internal clock that they may use for their judgements of durations. Our study thus suggests that the participants were perhaps in part aware of fluctuations of temporal estimation with arousal levels (Lamotte et al, 2014). Wearden, O'Donoghue, Ogden, and Montgomery (2014) provide examples of situations where passage of time judgements seem to be related to reported arousal levels.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…A long tradition (going back in formal models to Treisman, 1963) has proposed that people possess an arousalsensitive internal clock that they may use for their judgements of durations. Our study thus suggests that the participants were perhaps in part aware of fluctuations of temporal estimation with arousal levels (Lamotte et al, 2014). Wearden, O'Donoghue, Ogden, and Montgomery (2014) provide examples of situations where passage of time judgements seem to be related to reported arousal levels.…”
Section: Discussionmentioning
confidence: 64%
“…As regards the actual in-the-moment experience of passage of time (present time), Lamotte, Chakroun, Droit-Volet, and Izaute (2014) recently assessed, with a broad range of questions (106 questions), individuals' knowledge about different factors that may affect their experience of time passage. Despite the multitude of possible effects mentioned, statistical analyses extracted only two significant factors, one related to emotion and the other to attention.…”
Section: Introductionmentioning
confidence: 99%
“…Two inventories were employed to control for potential factors that could influence and explain performance and subjective ratings between groups: the German version of the international physical activity questionnaire (IPAQ; Ainsworth et al, 2000 ) assesses the amount of physical activity over the last week; with the Kurzfragebogen zur aktuellen Beanspruchung (short questionnaire on current demands, KAB; Müller and Basler, 1993 ) the awareness of everyday demands (and resulting stress level) is assessed; this inventory thus can be used as a proxy measure for the momentary well-being of an individual. Both physical activity ( Sysoeva et al, 2013 ) and emotional well-being ( Lamotte et al, 2014 ) have shown to influence time judgments.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, to address the question of age-related differences concerning the subjective passage of time over past time intervals of the last week, month, year, and ten years, additional questionnaires were employed, namely the scales for experiencing emotions (SEE) [ 38 , 39 ], a short form of the five factor personality inventory NEO-FFI (BFI-K; Big Five Inventory—Kurzform [ 40 ]) of the five factor personality inventory (the NEO-FFI), and the Barratt Impulsiveness Scale (BIS-11) [ 41 ]. Strong emotions in healthy individuals such as with trait-anxiety lead to a slower passage of felt time [ 42 ]; impulsive individuals more often overestimate duration and complain that time passes too slowly [ 5 ]. Relating to the two open questions mentioned above we aimed at conducting this exploratory study: (1) associating for the first time inventories relating to the time perspective with measures of time awareness; and (2) investigating potential factors related to age-related differences in retrospective judgments of various life spans.…”
Section: Introductionmentioning
confidence: 99%